Accelerated induction of experimental allergic encephalomyelitis in PL/J mice by a non-V beta 8-specific superantigen. - Soos, J M (1995)
Superantigens such as the staphylococcal enterotoxins can play an important role in exacerbation of autoimmune disorders such as experimental allergic encephalomyelitis (EAE) in mice. In fact, superantigens can reactivate EAE in PL/J mice that have been sensitized to rat myelin basic protein (MBP). The T-cell subset predominantly responsible for disease in PL/J mice bears the V beta 8+ T-cell antigen receptor (TCR). The question arises as to whether T cells bearing other V beta specificities are involved in induction or reactivation of EAE with superantigen. Thus, we have investigated the ability of a non-V beta 8-specific superantigen, staphylococcal enterotoxin A (SEA) (V beta specificities 1, 3, 10, 11, and 17), to induce EAE in PL/J mice that have been previously protected from disease by anergy and deletion of V beta 8+ T cells. PL/J mice were first pretreated with the V beta 8-specific superantigen staphylococcal enterotoxin B (SEB) and then immunized with MBP. These mice exhibited V beta 8-specific anergy and depletion and did not develop EAE, even when further treated with SEB. However, administration of SEA to these same mice induced an initial episode of EAE which was characterized by severe hindleg paralysis and accelerated onset of disease. In contrast to SEB pretreatment, PL/J mice pretreated with SEA did develop EAE when immunized with MBP, and after resolution of clinical signs of disease these mice were susceptible to relapse of EAE induced by SEB but not by SEA. Thus, superantigens can activate encephalitogenic MBP-specific non-V beta 8+ T cells to cause EAE in PL/J mice. These data suggest that superantigens can play a central role in autoimmune disorders and that they introduce a profound complexity to autoimmune diseases such as EAE, akin to the complexity seen in multiple sclerosis.